Catalyzing Pro-Social Purchases through Digital Brand Visibility: Insights from Bali’s Ethical Enterprise - Tjokorda Gde Agung Wijaya Kesuma Suryawan; Dayu Kade Indah Pratiwi; I Wayan Meryawan; I Komang Putra (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2026)
Ethical consumption is increasingly viewed as a behavioural driver of inclusive economic development. This study examines the influence of social media marketing on consumer purchase intention in the context of Beyond Organic (B’Onic), a micro-enterprise in Buleleng, Bali, which integrates social values into its commercial operations. Despite promoting ethical purchasing by funding a child welfare foundation, the enterprise struggles with declining consumer engagement due to weak brand visibility and limited digital interaction. The research explores the direct impact of social media marketing on purchase intention, the effect of brand awareness on purchase intention, and the mediating role of brand awareness in this relationship. Employing a quantitative approach, the study involved 110 purposively selected respondents, with data analysed using structural equation modelling. Findings reveal that social media marketing significantly enhances both brand awareness and purchase intention, with brand awareness acting as a substantial mediator. This study contributes to the literature on ethically positioned enterprise communication and offers practical insights for micro-enterprises seeking to scale social impact through digital strategies, strengthening their role in sustainable economic development.